2013
DOI: 10.1016/j.solener.2013.03.019
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for TiON sputtered surfaces showing accelerated antibacterial activity under simulated solar irradiation

Abstract: New evidence is reported for TiON sputtered polyester surfaces activated by sunlight irradiation leading to the accelerated bacterial inactivation in the minute range. The absorption in Kubelka-Munk units of the TiON film was observed to be directly proportional to the time of Escherichia coli inactivation as detected by diffuse reflection spectroscopy (DRS). TiON layers were characterized by electron microscopy and by high angle angular dark field (HAADF) showing the continuous coverage of the polyester fiber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Studies have shown tungsten oxide to have photocatalytic activity in visible light [ 36 ]. However, it has also been reported that the band gap energy of tungsten oxide nanoparticles is much larger than the energy of visible light illumination, therefore the generation of reactive species (like ●OH radicals) is likely to be the result of native defects [ 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ]. In the case of tungsten oxide, it can be said that the reduction in pathogenic microorganisms is the result of photokilling, whereby the reactive species damage the cell membrane causing the internal components to leak from the cells and are ultimately oxidised by the photocatalytic reaction [ 46 , 47 , 48 , 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown tungsten oxide to have photocatalytic activity in visible light [ 36 ]. However, it has also been reported that the band gap energy of tungsten oxide nanoparticles is much larger than the energy of visible light illumination, therefore the generation of reactive species (like ●OH radicals) is likely to be the result of native defects [ 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ]. In the case of tungsten oxide, it can be said that the reduction in pathogenic microorganisms is the result of photokilling, whereby the reactive species damage the cell membrane causing the internal components to leak from the cells and are ultimately oxidised by the photocatalytic reaction [ 46 , 47 , 48 , 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is a rising interest in the use photocatalytic materials for disinfection of surfaces, air, and water. Many studies have reported the application of titanium dioxide photocatalysts for water disinfection [83][84][85][86][87]. The investigation of antibacterial activity of TiO 2 -Cu coating using Escherichia coli showed that the survival rate decreased under very weak UV illumination intensity of 1 µW/cm 2 , suggesting impressive photocatalytic bactericidal activity [88][89][90][91].…”
Section: Antimicrobial Activity Of Oxides and Oxynitride Photocatalyt...mentioning
confidence: 99%
“…Rtimi et al investigated the mechanism and kinetics for the inactivation of E. coli over magnetron-sputtered TiON and TiON-Ag films. It was noted that the TiON films showed a stable performance over repetitive bacterial inactivation experiments [86]. On the other hand, the sputtered TiON-Ag catalysts shortened the Escherichia coli inactivation period to ∼55 min (short time under low-intensity visible light) due to Ag bactericidal properties [87].…”
Section: Antimicrobial Activity Of Oxides and Oxynitride Photocatalyt...mentioning
confidence: 99%
“…Frequently, it is a single-wavelength laser. Recently, broad-band solar light has been employed as alternative to laser light, for activating antibacterial surfaces including sulfur-doped TiO 2 , 13 N-doped TiO 2 thin films, 14 TiO 2 −nanoparticle-impreganated polymer matrix, 15 TiO 2 thin film coated with graphene oxide (GO) nanosheets, 16 TiO 2 thin film coated successively with Ag nanoparticles and Ag-TiO 2 nanocomposites, 17 Cu 2 O-nanoparticle-sensitized ZnO nanorod arrays on indium−tin−oxidecoated glass substrates, 18 sputtered TiON on polyester surfaces, 19 and textile coated with graphene/TiO 2 composites. 20 Though diverse, these photoactivated antibacterial surfaces usually act via the photocatalytic property of semiconductor materials such as TiO 2 upon irradiation by light in the UV and/or visible regions.…”
Section: ■ Introductionmentioning
confidence: 99%